A printability study of multichannel nerve guidance conduits using projection-based three-dimensional printing. (September 2022) - Li, Haibing; Yu, Kang; Zhang, Peng; Ye, Yensong; Shu, Qiang
Multichannel nerve guidance conduits (NGCs) replicating the native architecture of peripheral nerves have emerged as promising alternatives to autologous nerve grafts. However, manufacturing multichannel NGCs is challenging in terms of desired structural stability and resolution. In this study, we systematically investigated the effects of photopolymer properties, inner diameter dimensions, printing parameters, and different conditions on multichannel NGCs printability using projection-based three-dimensional printing. Low viscosity and rapid photocuring properties were essential requirements. A standard model was generated to evaluate multichannel NGC printed quality. The results showed that printing deviations decreased with increased mechanical strength and inner diameter. Subsequently, gelatin methacrylate (GelMA) NGCs was selected as a representative. It was found that printing conditions, including printing temperature, peeling, and shrinkage affected final NGC accuracy and quality. PC-12 cells cultured with the GelMA NGCs displayed non-toxic and promoted cell migration. Our research provides an effective, time-saving, and high-resolution technology for manufacturing multichannel NGCs with high fidelity, which may be used as reference templates for biomedical applications.